Humanitarian Cooperation in Sport on Space of the CIS as an Integration Factor - Natalya Mikhailovna Bogolyubova; Yulia Vadimovna Nikolaeva; Mikhail Alekseevich Bogolyubov (Управленческое консультирование)
Sports communications hold a firm place in system of the modern international relations. Many states consider sport, sporting achievements and sports contacts as the effective tool of soft force. Cooperation in sport is among priorities of foreign cultural policy of the Russian Federation and is considered by the government of our country as one of ways of formation of positive foreign policy image. In the article sports communications on space of the Commonwealth of Independent States as one of integration bases are analyzed. Work of the International Fund of humanitarian cooperation is especially noted, his contribution to strengthening of sports communications in the former Soviet Union is defined. The detailed review of the sporting events prepared with the assistance of Fund is presented in article. Many programs of regional cooperation of Russia and the CIS countries in the field of physical culture and sport have found reflection in work. Authors place particular emphasis on the actions which were taking place within Year of sport and a healthy lifestyle in the CIS (2012). The concept of Year of sport and a healthy lifestyle reflects humanitarian nature of this large-scale and multi-purpose action in which all states of the CIS have taken part. In the article also other forms of cooperation are considered: the international forums, conferences and symposiums devoted to a sports perspective. Sports cooperation is considered as a basis for development of dialogue in political and economic spheres. Authors draw a conclusion that cooperation of Russia with the CIS countries in sport promotes the solution of many social, humanitarian problems, popularizes a healthy lifestyle, influences formation of ecological thinking, makes a contribution to education of children, youths, youth, intensify cross-cultural dialogue in the former Soviet Union.